A novel reflectance-based aptasensor using gold nanoparticles for the detection of oxytetracycline1. Issue 19 (7th October 2015) - Seo, Ho Bin; Kwon, Young Seop; Lee, Ji-eun; Cullen, David; Noh, Hongseok (Moses); Gu, Man Bock
<x xml:space="preserve">Abstract</x> We present a novel reflectance-based colorimetric aptasensor using gold nanoparticles for the detection of oxytetracycline for the first time.